Figuring out this thing called femininity: Young women speak - Barns, Angela (Curtin University of Technology, 2001)
From wicked stepmother to feminist theorist, from fairy tale to dominant discourse, the question of ?the feminine? continues to inspire, perplex and arouse debate. For centuries, storytellers, philosophers, scientific investigators even economists have sought to ponder, theorize and diagnose the ?true nature? of the feminine; the essence of ?woman?. The following article reveals the findings of a feminist interpretive research inquiry undertaken with six, fifteen year old young women and their perceptions, experiences and expressions of femininity. Beginning with my own story of feminine adolescence, through the exploration of the young women?s stories of femininity, a kaleidoscope of meaning and representation is revealed. With a particular focus on the discourse of difference and its intersection with and perpetuation through the family, the media, peer groups, fashion and beauty, the young women?s experiences alert the reader to the many ways young women negotiate, construct and resist a feminine subjectivity.